New microsatellites for the Atacama Desert endemic Balsamocarpon brevifolium (Fabaceae). (11th June 2019) - Ravest, Gonzalo; León‐Lobos, Pedro; Aguirre, Carlos; Hernández, José; Bolados, Gustavo; Castro, María Herminia; Silva, Sergio; Hinrichsen, Patricio
Abstract : Premise: Algarrobilla ( Balsamocarpon brevifolium, Fabaceae) is an endemic xerophytic shrub restricted to the Atacama Desert in northern Chile. Extensive utilization of the region for coal production has endangered this species. Conservation efforts are underway, with genetic diversity analyses being key to the restoration of these populations. Methods and Results: Fifteen new microsatellite markers were developed for B. brevifolium and used to analyze three populations from the Atacama and Coquimbo regions in Chile. Microsatellites were highly polymorphic, with an average of 5.77 alleles per marker and an average level of expected heterozygosity of 0.72. These markers were evaluated and cross‐amplified on two related species ( Senna cumingii and Caesalpinia angulata ) with partial success. Conclusions: The development of this set of markers permits an extensive study of B. brevifolium populations for conservation purposes.